INFLUENCE OF STAFF MOTIVATION ON STAFFING OF THE STATE TREASURY SERVICE OF UKRAINE - Stativka, N.; Марченко, Людмила (Pressing Problems of Public Administration, 2019)
Formation of a highly professional institute of the State Treasury Service of Ukraine, provision of conditions for its effective functioning due to qualified personnel, capable of pursuing state policy properly, response to transformational challenges timely, is impossible without new approaches in the development of personnel motivation system. Staff motivation is a key reserve for improving the effectiveness of the performance of general and special management functions in the bodies of the State Treasury Service of Ukraine. In the article it was summarized the scientific approaches to understanding the term “staff motivation”, which are quite close in content and complementary. The components of wages and the types of civil servants’ bonuses was analyzed. The types of incentives for civil servants, which were divided in terms of moral, material, moral and material, are given. An analysis of the payroll of civil servants who are working in the Treasury Service of Ukraine (based on the example of the State Treasury Service of Ukraine in Kharkiv, Kharkiv region) was done. The main approaches to civil service recruitment were outlined, especially concerning the employment of vacant posts of civil servants the jurisdiction of whom extends to the territory of one or more districts, cities of regional importance. The separate articles and provisions of the Laws of Ukraine “About Civil Service”, adopted in different years, in terms of remuneration and career advancement in the civil service are considered. The analysis of staff turnover in the bodies of the Treasury Service of Ukraine was carried out.